Experimental Museology Institutions, Representations, Users - Achiam, Marianne; Haldrup, Michael; Drotner, Kirsten (Taylor & Francis, 2021)
Experimental Museology scrutinizes innovative endeavours to transform museum interactions with the world. Analysing cutting-edge cases from around the globe, the volume demonstrates how museums can design, apply and assess new modes of audience engagement and participation. Written by an interdisciplinary group of researchers and research-led professionals, the book argues that museum transformations must be focused on conceptualizing and documenting the everyday challenges and choices facing museums, especially in relation to wider social, political and economic ramifications. In order to illuminate the complexity of these challenges, the volume is structured into three related key dimensions of museum practice - namely institutions, representations and users. Each chapter is based on a curatorial design proposed and performed in collaboration between university-based academics and a museum. Taken together, the chapters provide insights into a diversity of geographical contexts, fields and museums, thus building a comprehensive and reflexive repository of design practices and formative experiments that can help strengthen future museum research and design. Experimental Museology will be of great value to academics and students in the fields of museum, gallery and heritage studies, as well as architecture, design, communication and cultural studies. It will also be of interest to museum professionals and anyone else who is interested in learning more about experimentation and design as resources in museums.